California Polytechnic School Band, 1916 (1916)
A photo of the first Cal Poly musical group, the 1916 band, which was organized the same year. This photo was taken at the same time as the photo used in the June 1916 Polytechnic Journal. Mr. Schlosser is standing as the director. The drum major is Joseph Gates. The following are listed in the Polytechnic Journal as participating in the band: Frank Kellogg, Tildo Tomasini, Lee Otto, George Harrison play Cornets. Joe Lynch, John McGillivray, Archie Plaskett play altos. Arthur Combs, Eugene Carey, Clifton Taylor, Leland McRae play Trombones. Arthur Scarlett and Everett Chandler play Baritons. Perry Martinsen plays Tuba. Fred Fingerhut plays cymbals. Theodore Erickson, Irwin Harvie, play drums.